Active learning - Mabrouk, Patricia Ann (American Chemical Society,Distributed by Oxford University Press, 2007)
The last decade has seen a dramatic increase in the application of active learning methods including problem-based learning, cooperative learning, and service learning and supportive strategies such as electronic methods to the college/university chemistry classroom and laboratory. This symposium series book focuses on the application of active learning methods in teaching analytical science, broadly defined, at both the undergraduate and graduate levels. The volume includes a wide range of examples of how these methods are being applied at public and private community colleges, four-year colleges, and graduate research universities in the United States and abroad. As such the strategies and materials described in the book should be of interest to analytical chemists, chemical educators, and chemistry teaching faculty and graduate students no matter their area of specialization